Analisa Penggunaan Batako Pada Rencana Anggaran Biaya Pembangunan Rumah Dhuafa Gampong Tambon Baroh Kecamatan Dewantara Kabupaten Aceh Utara - Sakura, Royanna; Idayani; Azizi, Abrar (Jurnal Vokasi Manajemen Dan Rekayasa Infrastruktur Sipil, 2024)
Brick material is used on non-structural walls, which are walls that do not support loads, only as a barrier if the wall is torn down, the building remains standing. Walls made of brick are much stronger than those built with red brick. The project used as the object of this research is a house for the poor located in Gampong Tambon Baroh, Dewantara District, North Aceh Regency. This research aims to compare the costs and implementation time related to the use of brick and red brick in the project. The cost analysis reference used in this research is using the 2022 AHSP. The calculation results state that the total cost of wall work using red brick is IDR. 50,387,730.40 with a construction time of 28 days, while using bricks it is Rp. 39,178,324.90 with a processing time of 17 days. Using bricks is cheaper than red bricks with the difference between the two being IDR. 11,209,405.50. The processing time is also much faster using brick compared to red brick, the time difference between the two is 11 days.